الحصانة القضائية لبعثات ووفود الدول الأعضاء في المنظمات الدولية - المبيض, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تساهم البعثات الدائمة لدى المنظمات الدولية ووفودها في إيجاد قنوات اتصال وتعاون جديدة وموازية للبعثات الدبلوماسية الثنائية أو التقليدية، فهذه الأخيرة قوامها علاقة ثنائية بين دولة موفدة وأخرى مستقبلة، محكومة باتفاقية فيينا للعلاقات الدبلوماسية لعام (1961) وبمبدأ المعاملة بالمثل، أما البعثات الدائمة للدول ووفودها فقوامها علاقة ثلاثية الأطراف بين دولة موفدة ومنظمة دولية ودولة مضيفة للمنظمة الدولية وهي ليست خاضعة لمبدأ المعاملة بالمثل، لأن هناك جملة من القواعد التنظيمية الناظمة للعلاقات داخل المنظمة الدولية، فكان من الضروري منح هذه البعثات والوفود حصانات وامتيازات لتسهيل نشاطاتها، حيث تعد الحصانة القضائية أساساً حيوياً حتى تتمكن البعثات والوفود لدى المنظمات الدولية من ممارسة اختصاصاتها وصلاحياتها ووظائفها بفعالية وبمعزل عن أي تقييد قد يصدر من جانب الدولة المضيفة، فهي حصانة وظيفية، هدفها توفير المناخ المناسب واجواء الحرية اللازمة، كي يتمكن ممثلو الدول الأعضاء من القيام بالوظائف المناطة بهم باستقلال وحياد .والحصانة القضائية لبعثات ووفود الدول لدى المنظمات الدولية تعني عدم خضوع ممثلي الدول لقوانين الدولة المضيفة، وتمنح لهم الحصانة القضائية لا لمنفعتهم الشخصية ولكن لتأمين استقلالهم في أداء مهامهم.ويتمتع ممثلو الدول في المنظمات الدولية بالحصانة القضائية سواء كانوا في اجتماعات الأجهزة الرئيسية للمنظمة أو الأجهزة الثانوية , أو في المؤتمرات التي تدعو المنظمة إلى عقدها .وهذه الحصانة تمنح للممثلين الدائمين لدى المنظمة الدولية بنطاق واسع, في حين أن مندوبي الدول الذين يوفدون لحضور مؤتمر أو تمثيل الدولة في أحد الاجتماعات , فهؤلاء يتمتعون بحصانة قضائية أدنى من تلك التي يتمتع بها الممثلون المؤقتون للدولة وأيضا دون ما هو ممنوح للممثلين الدائمين.Contribute to the permanent missions to international organizations and their delegations in finding communication and cooperation channels and new parallel diplomatic missions of bilateral or traditional, this is the last strong bilateral relationship between the state delegate and another receptor, it is governed by the Vienna Convention on Diplomatic Relations of the year (1961) and the principle of reciprocity, and the permanent missions of States and their delegations Vienna tripartite relationship between the state's envoy and international organizations and the host country of the international organization which is not subject to the principle of reciprocity, because there are a number of regulations governing the relationships within the international organization, it was necessary to give these missions and delegations immunities and privileges to facilitate their activities, where it is legal immunity vital foundation even able to missions and delegations to international organizations to exercise jurisdiction and powers and functions effectively and independently of any restriction has been issued by the host country, they are functional immunity, aimed at the right climate to provide the atmosphere needed freedom, so that the representatives of the Member States to carry out the functions assigned to them independence and impartiality.And judicial immunity for the missions and delegations of States to international organizations means not subject to the representatives of States of the laws of the host country, and they are granted immunity from prosecution is not for their own benefit but to secure their independence in the performance of their duties.